Efficient Market Hypotheses Controversy and Nigerian Stock Exchange Relations (American International Journal of Economics and Finance Research, 2020)
This study; Nigerian Stock Exchange and Efficient Market Hypothesis was done using All Share Index (ASI) with daily data from January 02, 2014 to May 20, 2019 (1333 observations) and annual data from 1985 to 2018 (34 observations) collected from the Nigeria Stock Market fact books. The study employed three analytical methods namely the unit root test, GARCH Model and the Autocorrelation cum patial autocorrelation method  for the assessment of weak form hypothesis on the daily and annual all share index in the Nigerian Stock market. The results of these evaluations indicated a significant relationship between the price series and their lagged values implying that stock price series do not follow a random walk process in Nigerian stock market. Thus, affirming that the Nigeria Stock Exchange is not efficient in weak form.  In the light of this, the researchers recommend that the supervisory and regulatory authorities should strengthen the Nigerian Stock Market through palliating its regulations pertaining to transparency of information management rules such as market barriers and stringent listing requirement, publication of accounts, notices of annual general meeting and the like.